Cleanse - Arguelles, Anna Doanne V.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
She has scars all over her body; scars from wounds inflicted by others, and scars from wounds inflicted by her self. All she ever learned as a child was how to swallow her pains and pretend everything was alright. Her mother would punish her, beat her up and plant lies in her head. Like she never deserved love from anyone, lies like she was to blame for anything that ever goes wrong, lies like she was evil, and lies like even God does not love her. So she grew up bitter and angry, believing in these lies. All the hate she had that she could not take out on her mother she took out on herself. She rebelled; she would do things she knew her mother would never approve of just to hurt her mother, not caring that she hurt herself more. She got a tattoo, and chose the design of the 'Madonna and Child'. A mocking dedication to her mother and her God. The situation at home never got better as she grew older; in fact, it was getting worse. Her mother was getting more and more deranged and she could not take it anymore. Fighting back is not an option because no matter how much she wanted to, it was not in her. She just couldn't because she was paralyzed from the power her mother had over her. So, she just runs away. Time passes and she seems to be getting on with her life. A life of her own, far away from her mother, far away from the home she escaped from, far away from the past which seems to be just like a horrible nightmare now. Then her life takes another turn. Her mother is dying and she has to come home. She does not want to, but she has to, and she does. So back she goes to the home she escaped from and sees how the tables have turned. She is the strong one now, and her mother is weak. Still, she feels nothing for her mother. No love, not even pity. All she ever felt for the woman was hate and all she ever did was keep it inside. Maybe she became too good at keeping her hate inside that it went away. Maybe all she really feels now is nothing, nothing at all. But a dream proves her wrong. In the dream, her mother is back to her old self, the cruel, angry woman she hated and feared. Only this time, she is not afraid of her anymore. She musters all the years of suppressed hate and takes action. In a rage, she kills the woman. She kills the source of all the hate she ever had. And she cannot believe it. Is she supposed to feel triumphant? Guilty? Afraid? All she knows is that she is confused. She wakes up. Looking at her is the dying woman she killed in her dreams, and all she can do now is help the woman die. Her mother asks to die in peace and she has no choice but to let her. Now all she is left with are the painful memories her mother gave her. All she is left with is the unresolved hate that will never have the chance to be retaliated. All she is left with are the wounds of the past that has never healed. She heals herself. By reopening the wounds and unleashing her Pandora's box of resentments, she begins. Through her art, she cleanses her wounds, and frees herself.
Vita.
Thesis (A.B. Film and Audiovisual Communication)--University of the Philippines Diliman
Keywords: Cleanse (Short films -- Philippines).; Self-consciousness (Awareness).